MANAGEMENT OF MARKETING PROJECTS OF A SHOE COMPANY «TRIEN» - E. Sanapalova (Вестник университета, 2017)
In article approaches to classification of projects, with reasons for allocation among them marketing projects are provided. Management of marketing projects depending on a lifecycle stage is considered. Examples of marketing projects of a shoe company «TRIEN» some of which were realized for the purpose of a process improvement of management are given.